A Comparative Tale of Peer-to-Peer, Client-to-Peer and Hybrid Networks in Federated Social Networking Sites in Educational Institutions - Mugoniwa, Beauty; Ngassam, Ernest Ketcha; Singh, Shawren (Indonesian Journal of Information Systems, 2024)
Due to increase in use of social networking sites(SNSs) in educational institutions, it has become common for institutions to adopt SNSs in academic institutions. Federated social networking sites(FSNSs) are powerful decentralisation platforms for educational activities. Qualitative scientific thorough review of relevant literature from multiple databases and qualitative survey from experts for Hybrid FSNS validation purposes. Peer-to-peer, client-to-server and hybrid networks present an excellent way of decentralising SNSs, however institution may need to scrutinise underlying functional and non-functional capabilities of each network architecture in order to come up with best platform for their institutions. Contemporary education need eLearning models that addresses critical needs for more effective and scalable educational solutions that can leverage benefits of SNSs while overcoming their limitations. Stakeholders should be able to make an informed decision as to which network to employ in their FSNSs, so that they can benefit from platforms’ specific educational opportunities.